2013
DOI: 10.1371/journal.pone.0071918
|View full text |Cite
|
Sign up to set email alerts
|

Translating Evidence for Low Back Pain Management into a Consumer-Focussed Resource for Use in Community Pharmacies: A Cluster-Randomised Controlled Trial

Abstract: BackgroundThis cluster-randomised controlled trial determined the effectiveness of an evidence-based, pamphlet intervention in improving low back pain (LBP)-related beliefs among pharmacy consumers.MethodsThirty five community pharmacies were randomised to three groups: pamphlet+education intervention [n = 11]; pamphlet only intervention [n = 11]; control: usual care [n = 13]. Eligibility requirements for clusters included: community-based pharmacies and proprietor participation consent. Pharmacy consumers (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Further, although the wait to access pain medicine services in Australia has been protracted for consumers, 17 timely access has been dramatically improved in WA owing to the introduction of a system-oriented MoC for pain services, 18 introduced in parallel with initiatives to build workforce and consumer capacity to better manage musculoskeletal pain syndromes. [19][20][21][22][23] A recent audit in WA identified positive uptake of all disease-group MoCs across the WA Health Services, particularly with respect to awareness and service planning, yet responders identified that sustainable implementation efforts were stymied by lack of resources to sustainably support implementation efforts. 24 In this regard, long-term sustainability and impact of MoCs will be dependent on their uptake and support by middle and senior health managers and policy makers and research providing evidence of their benefit for improving health outcomes and system efficiencies.…”
Section: Models Of Care: Do They Make a Difference?mentioning
confidence: 99%
“…Further, although the wait to access pain medicine services in Australia has been protracted for consumers, 17 timely access has been dramatically improved in WA owing to the introduction of a system-oriented MoC for pain services, 18 introduced in parallel with initiatives to build workforce and consumer capacity to better manage musculoskeletal pain syndromes. [19][20][21][22][23] A recent audit in WA identified positive uptake of all disease-group MoCs across the WA Health Services, particularly with respect to awareness and service planning, yet responders identified that sustainable implementation efforts were stymied by lack of resources to sustainably support implementation efforts. 24 In this regard, long-term sustainability and impact of MoCs will be dependent on their uptake and support by middle and senior health managers and policy makers and research providing evidence of their benefit for improving health outcomes and system efficiencies.…”
Section: Models Of Care: Do They Make a Difference?mentioning
confidence: 99%
“…Additionally, these data suggest that there is a “development to delivery” gap between accumulation of evidence‐based improvements in RA care and their implementation in clinical practice. This gap may be effectively bridged through policy‐into‐practice implementation initiatives . In addressing this gap for RA, we have previously determined the minimum disease‐specific knowledge and clinical skills required by community‐based physiotherapists to co‐manage people with RA in an evidence‐informed manner .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the provision of simple information is a cost-efficient intervention to improve sick leave outcomes 41. Similarly, the provision of written, consumer-focused information about pain at the primary care level has also been demonstrated to improve work-related fear beliefs in people with chronic low back pain54 and written information framed around a biopsychosocial rather than biomedical model is likely to be more effective 55…”
Section: Discussionmentioning
confidence: 99%